SANGKAN PARANING DUMADI SUMBU FILOSOFI YOGYAKARTA: DALAM LENSA FENOMENOLOGI-HERMENEUTIKA - Ajar Permono (Nun : Jurnal Studi Alquran dan Tafsir di Nusantara, 2021)
The Philosophy Axis of the Yogyakarta Palace reflects the human journey from a fetus, a baby, growing into a child, a teenager then an adult human being, having a family, aging and finally dying. The complete journey of human life is reflected in the philosophical expression of Sangkan Paraning Dumadi as the teachings of Islam are innalillahi wa innailaihi roji'un (QS. Al-Baqarah [2]:156). The philosophical concept of the heritage of the Javanese poets by Prince Mangkubumi is manifested in the form of the Yogyakarta Palace architecture. This article reviews the relationship of religion and culture with the Axis of Philosophy of Yogyakarta City within the framework of Javanese-Islamic typology through a phenomenology-hermeneutics of Husserlian-Heideggero-Gadamerian.